Public Policy and Private Interest : Ideas Self-Interest and Ethics in Public Policy - Chandler,J.A. (Newyork : Routledge, 2017)
Public Policy and Private Interest explains the complexities of the policy making process in a refreshingly clear way for students who are new to this subject. The key topics it explains are: How policy originates, is refined, legitimised, implemented, evaluated and terminated in the forms of theoretical models of the policy process; Which actors and institutions are most influential in determining the nature of policy; The values that shape the policy agenda such as ideology, institutional self-interest and resource capabilities; The outcome of policies, and why they succeed or fail; The main policy theories including the very latest insights from network theory and post-modernism; How national policy is influenced by globalization. The text is fully illustrated throughout with a broad range of national and international case studies on subjects such as the banking crisis, the creation of unitary authorities and global environmental policy and regulation. Combining both a clear summary of debates and theories in public policy and a new and original approach to the subject, this book is essential reading for students of public policy and policy analysis.
Keywords: Public Policy; Ethics